State and Hegemony in Nigeria: Implications for Environmental Politics - Emmanuel Olajide, Bamidele; Ojakorotu, Victor (International Journal of Criminology and Sociology, 2022)
This paper analyses the implication of state and hegemony on environmental politics in Nigeria. It argues that Nigeria as a British colonial creation is essentially a capitalist system that was invertedly created because unlike Western systems, it is a capitalist system that is run by non-capitalists. This implies that in Nigeria, there is a palpable absence of the state which is a creation of capitalists to coordinate other superstructures. This then explains why the political class in Nigeria comprises of fractious groups that are too preoccupied with politics and material survival and as such do not have hegemony. The import of absence of the state and dearth of hegemony in Nigeria is that environmental politics is uncoordinated with cases of Niger Delta and farmers-herdsmen crises demonstrating this reality. The paper concludes hegemony-induced environmental governance can ensure nationalistic values which would treat environmental and related issues with the urgency they deserve.